Agricultural Ethics - Burkhardt, Jeffrey; Comstock, Gary; Hartel, Peter G.; Thompson, Paul B. (Council for Agricultural Science and Technology (CAST), 2005)
This paper provides background on some ways in which ethics is applied productively to the food and agriculture system. Ethics may be a component in food safety and security, international trade, land-use policies, and animal welfare. Other topics considered include research ethics, public trust in science, and practical steps for institutionalizing ethics into agriculture. In addition to the scientific community, policymakers, agency leaders, and persons in the humanities and social sciences disciplines will find this study useful.
Keywords: Agriculture Ethics; Ethical; Food Safety; Security; International Trade